Velocity of explosively driven copper and aluminum plates with identical mass - Kučera, Jindřich; Šelešovský, Jakub; Kvapil, Jan; Pachman, Jiří (Univerzita Pardubice, 2020)
A Gurney velocity is often used to determine terminal velocity achievable by metal acceleration by explosive charge. The theory significantly simplifies the phenomena and does not include properties of the accelerated material. In this work we compare experimentally determined terminal velocities of copper and aluminum plates of exactly same mass accelerated by A-IX-1 charges and discuss the course of the metal acceleration. The experimental results are compared with results of Gurney approach and LS-DYNA numerical model for the same metal-explosive mass ratio. The velocity time histories were measured by photonic Doppler velocimetry.
Výbuchové urychlení měděných a hliníkových destiček se stejnou hmotností
Keywords: Gurney velocity; explosive acceleration; PDV; aluminum; copper; Gurneyho rychlost; urychlení výbuchem; PDV; hliník; měď